Differential Accumulation of Volatile Organic Compounds by Leaves and Roots of Two Guianese Philodendron Species, P. fragrantissimum Kunth and P. melinonii Brongn. Issue 4 (29th March 2017) - Joffard, Nina; Legendre, Laurent; Gibernau, Marc; Pascal, Laurence
Abstract : Leaf and root essential oils of two closely related but ecologically distant Philodendron species were extracted in natural conditions in French Guiana and analysed by GC/MS to i ) describe the blends of volatile organic compounds (VOCs) produced by those species and ii ) analyse species and environment‐based variations in extracts composition. A total of 135 VOCs were detected with a majority of aliphatic sesquiterpenes. P. fragrantissimum produced mainly β ‐bisabolene (on average 29.12% of the extract) as well as α ‐ and β ‐selinene (14.52% and 17.50%, respectively) while in P. melinonii, four aliphatic sesquiterpenes could alternatively be the main component: ( E )‐ β ‐farnesene (up to 91.42% of the extract), germacrene‐D (73.74%), β ‐caryophyllene (51.63%) and trans ‐ α ‐bergamotene (41.26%). A significant effect of species and organs on extracts composition was observed while the environment (sun exposure) only affected the relative proportions of monoterpenes and sesquiterpenes in roots of P . melinonii . These results are discussed in the light of the potential role of leaf and root terpenes in Philodendron species. Abstract :